CFD-modeling of steam separation in the drum-separator of a GM-50 boiler (E-50-3.9-440GM) (Інформатика. Культура. Техніка, 2025)
The processes accompanying evaporation have a complex physical nature. They are characterized by strong nonlinearity both in the dynamics and in the relationships of the thermophysical properties of the working medium. Key parameters, such as the degree of overheating or the local rate of vaporization, are difficult to accurately measure and predict. These difficulties determine the high requirements for the accuracy of numerical modeling and the justified choice of mathematical models that are able to reproduce the main physical mechanisms of vaporization under natural circulation conditions. The paper presents the results of a study of the process of water vapor separation in the space of a computer model of the drum-separator of the GM-50 boiler unit (E-50-3.9- 440GM), which was performed using the ANSYS Student program, which is free (since 2015) and is intended for solving introductory and educational tasks in an academic environment. The boundary conditions were set to the values of the speed of the steam-water mixture coming from the screen tubes of the GM-50 boiler. The object of the study is the processes of heat exchange and hydrodynamics that occur during the evaporation of the steam-water mixture in the tubes that screen the walls of the GM-50 (E-50- 3.9-440GM) fuel boiler and during its separation in the drum-separator of this boiler. The subject of the study is the thermodynamic parameters of the steam-water mixture in the natural circulation circuit of the GM-50 (E-50-3.9-440GM) boiler. The modeling allowed us to determine the flow rate of the working fluid in the boiler tubes and the location of the “evaporation mirror” in its drumseparator, which is critical for its functioning. Since there is no experimental data on the values of the steam content, the requirements for the operation of such drums were used to assess the adequacy of the model. The verification results show that the deviation values of the CFD model calculations from the values of the average volumetric steam content determined by the analytical method are in the range from 9 to 18%. This result is caused by both the assumptions of the analytical method and the limitations of the student version of ANSYS. In any case, the modeling allowed us to analyze the dynamics of steam generation in the boiler tubes of the natural circulation circuit of the GM-50 boiler (E-50-3.9-440GM) in conditions of uneven temperature field on the side walls of the boiler and to determine the parameters of the steam-water mixture at the outlet of the boiler tubes.
Keywords: Еvaporation; natural circulation; convective boiling; fuel plant; boiler